2005
DOI: 10.1074/jbc.m505036200
|View full text |Cite
|
Sign up to set email alerts
|

The DnaJ-domain Protein RME-8 Functions in Endosomal Trafficking

Abstract: Through a proteomic analysis of clathrin-coated vesicles from rat liver we identified the mammalian homolog of receptor-mediated endocytosis 8 (RME-8), a DnaJ domain-containing protein originally identified in a screen for endocytic defects in Caenorhabditis elegans. Mammalian RME-8 has a broad tissue distribution, and affinity selection assays reveal the ubiquitous chaperone Hsc70, which regulates protein conformation at diverse membrane sites as the major binding partner for its DnaJ domain. RME-8 is tightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(143 citation statements)
references
References 37 publications
10
131
2
Order By: Relevance
“…Preliminary functional analysis indicates that the expression of DNAJC13 p.Asn855Ser in COS7 cells leads to accumulation of TF in endosomal compartments, suggesting interference with endosomal compartmentalization or trafficking as the pathological mechanism of disease. The importance of DNAJC13 function in endosomal trafficking is evident from several studies showing alterations in trafficking of well-known retromer cargos when its function is perturbed (13,20). The function of retromer itself is linked to PD through the observation that mutations in another retromer subunit, VPS35, can cause familial parkinsonism (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary functional analysis indicates that the expression of DNAJC13 p.Asn855Ser in COS7 cells leads to accumulation of TF in endosomal compartments, suggesting interference with endosomal compartmentalization or trafficking as the pathological mechanism of disease. The importance of DNAJC13 function in endosomal trafficking is evident from several studies showing alterations in trafficking of well-known retromer cargos when its function is perturbed (13,20). The function of retromer itself is linked to PD through the observation that mutations in another retromer subunit, VPS35, can cause familial parkinsonism (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the physiological consequence of the DNAJC13 p.Asn855Ser mutation, we assessed the uptake of transferrin (TF), a membrane receptor ligand that is constitutively internalized and recycled through the endosome pathway (12,13). COS7 cells expressing a GFP control, wild-type (WT) or mutant DNAJC13 were exposed to 568-conjugated TF for 1 h at 48C and either fixed immediately (T0) or after a 40 min incubation at 378C (T40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the clathrin associated Hcs70 cochaperone RME-8 regulates endosomal trafficking of STx (Popoff et al 2009) whilst having no effect on the transport of cholera toxin (Girard et al 2005). …”
Section: Toxin Intracellular Trafficking To the Endoplasmic Reticulummentioning
confidence: 99%
“…Likewise, studies of rme-8 mutants in Drosophila displayed blockage in the internalization of the Bride of Sevenless receptor causing the formation of the rough eye phenotype (5). RME-8 has not only been shown to be highly conserved in the animal kingdom (6,7), but it is also present in plants, where studies in Arabidopsis thaliana have demonstrated that RME-8 mutants exhibit gravitropism defects and associate with endosomal structures (8). Finally, a recent study has determined that a gain of function mutation in RME-8 correlates with Parkinson disease (9), highlighting the importance of studying RME-8 biology in more detail.…”
mentioning
confidence: 99%